Intensive agriculture and soil quality: challenges for sustainable development in Sinaloa - Cuadras Berrelleza, Aldo Alan; Peinado Guevara, Víctor Manuel; Peinado Guevara, Héctor José; López López, José de Jesús; Barrientos, Jaime Herrera (Revista Mexicana de Ciencias Agrícolas, 2021)
In a regional dimension, two key factors of agricultural activity in Guasave, Sinaloa, Mexico that directly influence sustainable rural development are analyzed: intensive agriculture and soil quality. This research was designed as a qualitative descriptive study of this productive branch, for this purpose, 164 interviews with producers were conducted and various documents with information on the sector were analyzed, such as technical reports and bulletins. It was found that intensive agriculture predominates in the study area, with traditional production practices and patterns, such as gravity irrigation systems and excessive use of agrochemicals, which presupposes agricultural management that goes against the sustainable context. Action-research is required for the implementation of resilience strategies with a sustainable approach, aligned with the adequate environmental governance of the activity and the needs of the sector, since problems such as the loss of soil fertility, an increase in salinity and erosion in some agricultural farms continue to be observed.
Keywords: agricultural practice; production patterns; sustainable rural development